The common ground is epistemic violence: towards a social epistemology-based lens on the neoliberal-fascist nexus - Kather, Cara-Julie (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This paper offers a framework based on Social Epistemology and developed for interdisciplinary applicability in Social Theory, Political Theory and Cultural Studies to tend to the task of developing a nuanced lens on intricacies of neoliberalism and fascism. The core argument this paper establishes is that neoliberal-fascist convergence arises precisely at instances of meaning-making that are instances of epistemic violence. To connect Social Epistemology to discourse on the neoliberal-fascist nexus, I employ Miranda Fricker's framework of hermeneutical resources to then develop the notion of Hermeneutical Connectivity to explore the neoliberal-fascist nexus in its overlappings regarding social interpretation. In a second step, I propose my understanding of the framework Epistemic Violence to further analyse these hermeneutical overlappings. My core argument here is that the notion of epistemic violence can be applied to both name and analyse the interconnectivity of neoliberalism and fascism. I explore essentialism with regard to gender and race as a case study to exemplify how these Social Epistemology-based frameworks may be applied to the case of the neoliberal-fascist nexus.
Keywords: Epistemic Violence; Hermeneutical Resource; Philosophy of Race; Philosophy of Gender; Essentialism; Neoliberal-Fascist Nexus; Feminist Epistemology; Feminist Anti-Fascism